Non‐invasive in vivo monitoring of transplanted stem cells in 3D‐bioprinted constructs using near‐infrared fluorescent imaging - Soon Hee Kim; Jin Seon Kwon; Jae Gu Cho; Kate G. Park; Tae Hyeon Lim; Moon Suk Kim; Hak Soo Choi; Chan Hum Park; Sang Jin Lee (Wiley, 2021)
Abstract Cell‐based tissue engineering strategies have been widely established. However, the contributions of the transplanted cells within the tissue‐engineered scaffolds to the process of tissue regeneration remain poorly understood. Near‐infrared (NIR) fluorescence imaging systems have great potential to non‐invasively monitor the transplanted cell‐based tissue constructs. In this study, labeling mesenchymal stem cells (MSCs) using a lipophilic pentamethine indocyanine (CTNF127, emission at 700 nm) as a NIR fluorophore was optimized, and the CTNF127‐labeled MSCs (NIR‐MSCs) were printed embedding in gelatin methacryloyl bioink. The NIR‐MSCs‐loaded bioink showed excellent printability. In addition, NIR‐MSCs in the 3D constructs showed high cell viability and signal stability for an extended period in vitro. Finally, we were able to non‐invasively monitor the NIR‐MSCs in constructs after implantation in a rat calvarial bone defect model, and the transplanted cells contributed to tissue formation without specific staining. This NIR‐based imaging system for non‐invasive cell monitoring in vivo could play an active role in validating the cell fate in cell‐based tissue engineering applications.